Emissivity measurement of the ITER-like plasma facing components of the WEST phase 2: Pre-exposure measurements and first WEST exposure. (October 2022) - Gaspar, J.; Rigollet, F.; Ehret, N.; Anquetin, Y.; Bernard, E.; Corre, Y.; Diez, M.; Firdaouss, M.; Houry, M.; Loarer, T.; Martin, C.; Missirlian, M.; et al.
Highlights: Emissivity variability for a serial production of ITER-like divertor components. Emissivity evolution due to high heat flux tests. Non-uniform emissivity along ITER-like divertor components after exposure in WEST. Abstract: This paper summarizes the emissivity measurements performed on the shaped ITER-like plasma facing units (PFU) of the WEST lower divertor installed for the second phase of WEST. Laboratory measurements before their installation in WEST, as well as measurement of one ITER-like PFU after exposure to an experimental campaign are shown. The measurements of 24 standard ITER-like PFU show the emissivity variability from 0.07 to 0.2 even for a serial production. Measurements performed after high heat flux tests (10 MW/m 2 cycles) on two different facilities show the emissivity modification induced by this heat load capability test with mainly a decrease of the emissivity in the heat load area. Finally, the exposed ITER-like PFU exhibit a complex pattern with strong emissivity variation from 0.05 in the net erosion area at the strike point locations up to 0.85 in the deposition area close to the strike point location.